PELATIHAN PENGGUNAAN MENDELEY BAGI MAHASISWA ANGKATAN 2021 DAN 2022 JURUSAN PBSI, FKIP, UHO - Sumiman Udu; Fahruddin; Sri Suryana Dinar; Andi Muh. Ruum Sya'baan (JESASI (JURNAL EDUKASI, SAINS, DAN INOVASI), 2024)
This Community Service Program is entitled "Training on the Use of Mendeley for Students Class of 2021 and 2022, Department of Indonesian Language and Literature Education, FKIP, UHO". In general, the aim of this service activity is through training activities Students can easily use the Mendeley application to prepare their final assignments, especially how to quote expert opinions and write references automatically through the Mendeley application. Implementation of service is carried out in three stages, where the first stage is the preparation stage. In the preparation stage, the service group conducted a preliminary survey to see field conditions regarding the knowledge of PBSI students class of 2021 and 2022 regarding the Mendeley application. The next stage of activity is training related to the use of the Mendeley application. The final stage is the evaluation stage, at this stage an evaluation of the results achieved by the training participants is carried out. Further input and improvements can be made at this stage. Evaluation is provided by collecting data obtained from training activities. Data was taken by summarizing students' understanding regarding the use of the Mendeley application. The implementation of community service activities is packaged using a training approach. Activities are carried out using lecture, discussion and practice methods.